A Study on the Matching Efficiency of Malaysia’s Labor Market during the Covid-19 Pandemic using the DEA-Malmquist Productivity Index - Jamaludin, Salwaty; Abdul Hamid, Kamarul Hidayah; Abdul Malek, Nazurah; Khan, Muhammad Zaheer; Shakrein Safian, Sharul Shahida; Shaharuddin, Norhasimah (Information Management and Business Review, 2023)
This paper analyses the matching efficiency of the Malaysian labor market during the COVID-19 pandemic. Employing Malmquist DEA, the results indicate that from January 2020 to December 2021, the average total factor productivity change is 0.967. TFPCH declined and had an average growth rate of -3.3% during the sample period. Decomposing TFPCH into technical change (TECHCH) and efficiency change (EFFCH), low TECHCH, with an average growth rate of -10.2%, is the main reason why TFPCH is far from the effective frontier. The TFPCH of the mining and quarrying industry is the highest, with an average growth of 18.7%. The TFPCH of both manufacturing and construction industries are the lowest with average annual growths of -1.7% and -7.6% respectively. Overall, it can be concluded that one of the main drivers to enhance the matching efficiency of the labor market is technical change or technological progress. One way is to strengthen online platforms that can help the firm or industry to match job vacancies to job seekers, even during economic shocks.